(untitled) (Bangladesh Medical Journal, 2023)
Premature rupture of membranes (PROM) is characterized by the spontaneous rupture of chorioamniotic membranes more than one hour before the onset of labor. This condition typically arises spontaneously in most cases, affecting a significant portion of pregnancies. Notably, PROM can also occur in full-term pregnancies. This cross-sectional follow-up study was conducted among pregnant women had premature rupture of membranes and experiencing Caesarean Section (CS) in the department of Obstetrics and Gynaecology of Dhaka National Medical College Hospital (DNMCH), Dhaka, Bangladesh during the period of March to August 2011. The main aim of the study was to find out the indication and outcome of pregnant women with PROM and completed CS. A total of 90 data were collected purposively from all pregnant women more than 28 weeks of gestational age with PROM admitted in the Department of Obstetrics and Gynaecology, DNMCH, Dhaka for labour and underwent CS during study period. The data were collected using a semi-structured data sheet through direct questioning of the patients and physical examinations. Daily follow-ups were conducted until the patients were discharged, and data were also obtained from the clinical records of the patients. PROM patients encompassed all age groups, with ages ranging from 18 to 38 years. The overall educational level of the participants was low, with less than two-third (61.1%) belonging to the low socio-economic status. The average gestational age was 36.65 weeks, with 53.3% being primigravida, 45.6% being multigravida and grand multipara was 1 (1.11%). Only two had multiple pregnancies, and 11 respondents had experienced per vaginal bleeding. During previous gestations, 20 had a history of Caesarean section, 12 had experienced abortion, and 2 had previous cases of PROM. Nutritional deficits were found in 36.7% of patients, Pregnancy Induced Hypertension (PIH) in 35.6%, infections in 12.2%, and chronic hypertension in 5.6%. Four foetuses were in breech presentations, one had a single compound presentation, and two had a transverse or oblique lie. All the women were experiencing gushing of fluid per vagina, with one-fifth (20.0%) having meconium-stained and 12.2% blood-stained vaginal discharge. Attempts to prolong pregnancy were not very successful, with the longest duration being 75 hours. Caesarean sections had to be performed in all cases, with 34.4% within 24 hours and 41.2% within the next 24 hours. Elective caesarean sections following PROM were 28.9%. Indications for emergency caesarean section included a previous history of Caesarean section in 19 cases, foetal distress was found in 18 cases, failed induction in 7 cases, chorioamnionitis in 6 cases, foetal malpresentation was in 5 cases, and other reasons in 9 cases. More than one-third (35.56%) respondents had morbid condition to complicate the postpartum period. Among the complications, 21.11% suffered from wound infection; followed by puerperal sepsis 8.89% and postpartum haemorrhage 5.56%. At termination, all 92 foetuses were alive, but 6 babies had an Apgar score <7 at 5 minutes after delivery, 30.4% of babies had low birth weight and 73.9% were in good condition, whereas 26.1% were admitted in neonatal ward, and out of the admitted 7 died with neonatal sepsis being the primary cause of death. A better understanding of the diagnosis babies and management of PROM will enable obstetric care providers to optimize perinatal outcomes and minimize neonatal morbidity and mortality. Therefore, this study finds the indication and outcome of caesarean section in pregnant women experiencing PROM. Bangladesh Med J. 2022 May; 51(2): 45-53